BIOCHEMICAL METHODS OF INVESTIGATIONS IN DIAGNOSTICS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Biochemical methods of research in diagnostics - methods of research of chemical components of biological fluids, cells and tissues, as well as processes of transformation of substances and energy occurring in the human body in norm and pathology [20,21].